Assembly, accretion, and break-up of the Palaeo-Mesoproterozoic Columbia supercontinent: record in the North China Craton revisited - Zhao, G.; Li, S.; Sun, M.; Wilde, Simon (Bellwether Publishing, 2011)
Columbia is a Palaeo-Mesoproterozoic supercontinent that was assembled during global 2.0–1.8 Ga collisional events, underwent long-lived, subduction-related accretion at key continental margins in the period 1.8–1.3 Ga, commenced to fragment ~1.6 Ga ago, and finally broke up at ~1.3 Ga. Similar to most other cratonic blocks (Laurentia, Baltica, Siberia, Amazonia, West African, South Africa, India, Australia, and Antarctica), the North China Craton records the history of assembly, accretion, and break-up of the Columbia supercontinent. New data indicate that the Archaean to Palaeoproterozoic basement of the North China Craton was assembled by microcontinental blocks along three Palaeoproterozoic collisional belts: the Khondalite Belt, the Jiao-Liao-Ji Belt, and the Trans-North China Orogen. The Khondalite Belt was formed by collision between the Yinshan and Ordos blocks and was amalgamated to form the Western Block at ~1.95 Ga. The Eastern Block underwent Palaeoproterozoicrifting at 2.2–1.9 Ga to break-up into the Longgang and Nangrim blocks; then the rift basin/incipient ocean closed attending subduction and collision to form the Jiao-Liao-Ji Belt at ~1.9 Ga. Finally, the Western and Eastern blocks collided along the Trans-North China Orogen to form the coherent basement of the North China Craton at ~1.85 Ga. Following this final assembly, the North China Craton underwent subduction-related accretion at its southern margin during the period 1.78–1.45 Ga, forming the Xiong’er volcanic belt. At 1.6–1.2 Ga, the northern margin of the North China Craton underwenta rifting event that led to separation of the craton from other cratonic blocks of the supercontinent Columbia, forming the 1.6–1.2 Ga Zhaertai-Bayan Obo rift zone and associated 1.35 Ga mafic sills along the northern margin of the craton. These data indicate that in any configuration of Columbia, the southern margin of the North China Craton must have faced an open ocean, whereas its northern margin was connected to another continental block.